Odpowiedź:
Szczegółowe wyjaśnienie:
e) 3x - 5 / 2 - 5x - 1 / 10 = 0
5 (3x - 5) / 10 - 5x - 1 / 10 = 0
15x - 25 / 10 - 5x - 1 / 10 = 0
15 x - 25 - 5x - 1 / 10 = 0 / * 10
15 x - 25 - 5x - 1 = 0
10x - 26 = 0
10x = 26 / : 10
x = 2,6
f) x / 2 = 2/5 (4 - x) - 4
x / 2 = 8/5 - 2/5 x - 4
x / 2 = 8/5 - 20/5 - 2/5x
x / 2 = -12/5 - 2/5 x / * 2
x = -24/5 - 4/5 x
x + 4/5 x = - 24/5
5/5 x + 4/5 x = -24/5
9/5 x = - 24/5 / * 5
9x = -24 / : (-9)
x = 24/9 = 2 6/9 = 2 2/3
g) 2x - 1/5 - x - 2 / 2 = 0,7x
2 (2x - 1) / 10 - 5 (x - 2) / 10 = 0,7x
4x - 2 / 10 - 5x + 10 / 10 = 0,7x
4x - 2 - 5x + 10 / 10 = 0,7x
-x + 8 / 10 = 0,7x / * 10
-x + 8 = 7x
8 = 8x / : 8
1 = x